Geographical Information System (GIS) development for Licensing and Enforcement Department (LED) of MBSA (GIS-LED) using spatial data analysis / Muhammad Zabidi Mohd Zain … [et al.] - Mohd Zain, Muhammad Zabidi; Mokhsin @ Misron, Mudiana; Abdul Karim, Norisan; Ahmad, Nor Diana; Redzuan, Fauziah (Research Innovation Business Unit, 2014)
This project aims to develop a Geographical Information System for Licensing and Enforcement Department (GISLED) of Majlis Bandaraya Shah Alam (MBSA). The functionality of this system is to help the department monitor the information license registration and renewal for enterprise signboard license, billboard license and bunting license in Shah Alam. The information about licenses is basically location based so the information system that is based on geographical aspects and location is needed. Geographical Information System (GIS) are software system that is used when capturing, storing, managing and displaying spatial data. The ability of GIS to capture information such as the location of offenders, on to a GIS has important implications for the rapid and timely accumulation of spatial data and the conduct of the analysis. In order to develop the system, some analysis must been made using the spatial data analysis, and the system must integrate with spatial database management system.